Pengaruh Komite Audit dan Pertumbuhan Penjualan terhadap Tax Avoidance dengan Ukuran Perusahaan sebagai Variabel Moderasi - Chandra Ningsih; Lodang Prananta Widya Sasana (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Tax as an obligation that must be paid by companies that are used to support the growth and development of the country for the welfare of the community, but not infrequently companies practice tax avoidance, because taxes can reduce company income. This study aims to scientifically examine the effect of the audit committee and sales growth on tax avoidance with company size as a moderating variable in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This type of research uses a purposive sampling method, namely with 150 observation data from 30 selected companies. The type of data used in this study is secondary data using quantitative research methods. Testing in this study uses e-eviews 12 student lite version. The results of this study indicate that simultaneously the audit committee and sales growth have an effect on tax avoidance, partially the audit committee has an effect on tax avoidance, sales growth has no effect on tax avoidance, company size is able to moderate the audit committee on tax avoidance, company size is unable to moderate sales growth on tax avoidance